OPTIMIZING CRIME RESOLUTION: EVALUATING THE POWER OF AUTOMATED FINGERPRINT IDENTIFICATION SYSTEM IN TACKLING BUSINESS ROBBERIES IN CARLETONVILLE, GAUTENG PROVINCE - Isaack L. Macuphe; Dee Khosa; Adewale A. Olutola (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This research examines the South African Police Service (SAPS) and the challenges faced in achieving satisfactory conviction rates and employing effective investigation methods for business robbery cases. Employing a qualitative research approach, the study involved a comprehensive literature review and structured interviews with fingerprint experts and data processors affiliated with the Carletonville SAPS. The primary aim was to investigate and analyze potential solutions to the identified issues. The study reveals that the implementation of the Automated Fingerprint Identification System (AFIS) represents a viable solution. The findings indicate that AFIS technology has the potential to significantly enhance the investigation and prevention of various criminal activities, including theft, business robberies, and homicides. AFIS facilitates the rapid matching of biometric markers and fingerprints, enabling the swift identification and linking of suspects to specific crimes. While acknowledging both the strengths and limitations of AFIS, the research underscores its substantial potential to revolutionize law enforcement practices. By integrating AFIS, law enforcement agencies can achieve notable improvements in the efficiency and accuracy of criminal investigations. This research provides a foundational step toward the development and implementation of effective strategies for crime prevention and combat in South Africa.